Degradation of aqueous Disperse Orange 25 by supercritical water oxidation - Sogut, Onur Oe; Akgun, Mesut (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2008)
Oxidation of aqueous solutions of CI Disperse Orange 25 was studied in a continuous flow reactor that was operated between 400 and 600 degrees C at a fixed pressure of 25 MPa. The dye total organic carbon (TOC) concentrations were in the range of 35.0 and 174.8 mmolL(-1) in the feed stock solution. Hydrogen peroxide (H2O2) was used as an oxygen source and the oxidant concentrations were between 147 and 735 mmolL(-1) in the feed stock solution. The results demonstrated that the supercritical water oxidation process decreases the TOC up to 99.96% in very short reaction times (at residence times of 4-12 s). According to the wastewater and oxidant concentrations, the global rate expression was regressed from the complete set of data. As a result of regression analysis, the pseudo first-order global rate expression according to the wastewater concentration was determined with an activation energy of 40.181 (+/- 1.1) kJmol(-1) and a pre-exponential factor of 218.7 (+/- 2.1) s(-1) to a 95% confidence level.
Keywords: supercritical water oxidation; textile wastewater; Disperse Orange 25; TOC; CATALYTIC WET OXIDATION; WASTE-WATER; AZO-DYE; REACTIVE DYES; DECOLORIZATION; OZONATION; DECOMPOSITION; KINETICS; Environmental Sciences & Ecology